Myelin Oligodendrocyte Glycoprotein Antibody Associated Transverse Myelitis - Chroustová, Iveta; Mareš, Miroslav; Ungermann, Leoš; Ehler, Edvard (Acta medica (Hradec Kralove), 2019)
Antibodies against myelin oligodendrocyte glycoprotein cause inflammatory lesions of central myelin - in optic nerves, of the brainstem, and spinal cord. There are characteristic changes of CNS white matter, protein-cytological association in cerebrospinal fluid, MOG IgG antibodies, a very important differential diagnosis and a relatively mild course.
Keywords: Autoantibodies; Myelitis, Transverse; glykoprotein v myelinu oligodendrocytů; dospělí; transverzální myelitida; Adult; Myelin-Oligodendrocyte Glycoprotein; inflammation; Humans; antibodies; myelin oligodendrocyte glycoprotein; mužské pohlaví; Male; lidé; autoprotilátky; spinal cord